The Kalimantacin Polyketide Antibiotics Inhibit Fatty Acid Biosynthesis in Staphylococcus aureus by Targeting the Enoyl‐Acyl Carrier Protein Binding Site of FabI. Issue 26 (14th April 2020) - Fage, Christopher D.; Lathouwers, Thomas; Vanmeert, Michiel; Gao, Ling‐Jie; Vrancken, Kristof; Lammens, Eveline‐Marie; Weir, Angus N. M.; Degroote, Ruben; Cuppens, Harry; Kosol, Simone; Simpson, Thomas J.; Crump, Matthew P.; et al.
Abstract: The enoyl‐acyl carrier protein reductase enzyme FabI is essential for fatty acid biosynthesis in Staphylococcus aureus and represents a promising target for the development of novel, urgently needed anti‐staphylococcal agents. Here, we elucidate the mode of action of the kalimantacin antibiotics, a novel class of FabI inhibitors with clinically‐relevant activity against multidrug‐resistant S. aureus . By combining X‐ray crystallography with molecular dynamics simulations, in vitro kinetic studies and chemical derivatization experiments, we characterize the interaction between the antibiotics and their target, and we demonstrate that the kalimantacins bind in a unique conformation that differs significantly from the binding mode of other known FabI inhibitors. We also investigate mechanisms of acquired resistance in S. aureus and identify key residues in FabI that stabilize the binding of the antibiotics. Our findings provide intriguing insights into the mode of action of a novel class of FabI inhibitors that will inspire future anti‐staphylococcal drug development. Abstract : Combating MRSA : The kalimantacin antibiotics mimic the conformation of the natural fatty acyl substrate to inhibit the activity of the essential enoyl‐ACP reductase enzyme FabI in Staphylococcus aureus . The findings of this study provide insights into the mode of action of this novel class of FabI inhibitors.